Professional Competence of Indonesian Language Teachers in Senior High Schools: Perspectives of Senior High School Students - Razak, Nur Khadijah; Nurfaizah, Andi; Rahayu, Sri (Universitas Pendidikan Ganesha, 2024)
The current problem is the lack of interest of students to enter Indonesian language colleges. There are 67.70% do not understand the meaning of Indonesian, 75.45% are less interested in majoring in Indonesian. There is a gap between expectations and reality in the field. The purpose of the study was to analyse the relationship between teacher knowledge and student understanding in the learning process. Quantitative method with survey type. The research sample was 756 people. The sampling technique was random sampling. Data collection technique with instruments. The instrument has been developed and is valid with a total of 80 items. The instrument is assessed on a Likert Scale of 1-5 points. The instrument is distributed using a google link from. The analysis technique with descriptive statistics with the help of SPSS Version 29.0 by looking at the mean, percentage, standard deviation and seeing the relationship. The results found that the level of knowledge and understanding of teachers regarding Indonesian language lesson content is in the high category. It was also found that the relationship between Indonesian language teacher competence in understanding and knowledge is in the high and significant category and in mastering Indonesian language learning content in high schools. The conclusion is that the professional competence of teachers is good, but in its implementation, it is still minimal.